AutiPECS: Mobile Based Learning of Picture Exchange Communication Intervention for Caregivers of Autistic Children - Ahmad Sofian, Shminan; Rabiatu Adawiyah, Adzani; Sabariah, Sharif; Lee, Nung Kion (2017)
The goal of this study is to develop and assess a mobile-based learning concerning the Picture Exchange Communication (PECS) for Autism Spectrum Disorder (ASD) children’s caregivers. Being an inexpensive intervention, the PECS has been proposed by other parents who have practised it on their children with non-verbal and behavioral disabilities. The underlying motivator for this mobile application is to guarantee that autistic children can have a better alternative intervention through the PECS approach so that they would not rely on the therapist a great deal or go to the autism center which is often costly. Fundamentally speaking, this mobile application elaborates on the user requirements which include PECS introduction, the characteristics, initial preparations, strategies and the activities. Instructional System Design (ISD) functions as the methodologies that help create the mobile-based learning. The system design has five stages namely the analysis, design, development, implementation and evaluation. These stages better known as ADDIE have the purpose to ensure that user will attain the goals of the instruction for the entire process. Lastly, to examine the content and the user interface design for this mobile application, a formative evaluation was conducted, aided by the usability testing by questionnaires and short instructed interviews. With the application of the ADDIE principles and guideline of Human-Computer Interaction (HCI), the best combination of causes of the AutiPECS had been developed properly. In sum, this research has been found to achieve the objectives. The content had been assessed by the expert, and the caregivers know how to adopt D.I.Y concepts as they are working on the learning materials. Future works may also be able to take more advantage of the AutiPECS 2.0 version where they can develop the mobile-based learning of PECS in the extended content and pay more attention to more specific case studies so that the caregivers know how to use PECS with the special children everyday.